2021
DOI: 10.1136/bmjopen-2021-050303
|View full text |Cite
|
Sign up to set email alerts
|

What is the extent of COVID-19 vaccine hesitancy in Bangladesh? A cross-sectional rapid national survey

Abstract: ObjectivesTo assess COVID-19 vaccine hesitancy in Bangladesh and identify population subgroups with higher odds of vaccine hesitancy.DesignA nationally representative cross-sectional survey was used for this study. Descriptive analyses helped to compute vaccine hesitancy proportions and compare them across groups. Multiple logistic regression analyses were performed to compute the adjusted OR.SettingBangladesh.ParticipantsA total of 1134 participants from the general population, aged 18 years and above partici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
59
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 32 publications
7
59
3
Order By: Relevance
“…The study also found that 2.9% of the respondents would discourage their family members from receiving the vaccination, and 3% forbid their family members. Overall, this study found a prevalence of 46.2% hesitancy to receive the COVID-19 vaccine, which is a higher estimate than Kabir et al (31%) [ 20 ], Ali and Hossain (32.5%) [ 13 ], and Mahmud et al (38.8%) [ 21 ]. This higher prevalence may partly be explained because the existing studies were conducted in Bangladesh [ 13 , 20 , 21 ] as a rapid assessment of the situation, resulting from participant selection bias.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The study also found that 2.9% of the respondents would discourage their family members from receiving the vaccination, and 3% forbid their family members. Overall, this study found a prevalence of 46.2% hesitancy to receive the COVID-19 vaccine, which is a higher estimate than Kabir et al (31%) [ 20 ], Ali and Hossain (32.5%) [ 13 ], and Mahmud et al (38.8%) [ 21 ]. This higher prevalence may partly be explained because the existing studies were conducted in Bangladesh [ 13 , 20 , 21 ] as a rapid assessment of the situation, resulting from participant selection bias.…”
Section: Discussionmentioning
confidence: 66%
“…We used the following formula to calculate the sample size: (Z 2 pq/e 2 )Deff*NR. We used Z-score for 95% confidence interval (Z = 1.96), prevalence (p) of willingness to accept a COVID-19 vaccine from an earlier study (p = 0.325) [ 13 ], margin of error (e = 0.03); design effect (Deff = 1.6) for sampling variation; and a non-response rate (NR = 10%). The calculated sample size was 1635, distributed for face-to-face and online surveys using a 2:1 ratio considering the country’s digital divide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned before the difference was expected because of more literate responders in those studies. Our acceptance rate is even lower than our neighboring countries and unfortunately is far lower than what is required for herd immunity [6,8,10,20].…”
Section: Discussionmentioning
confidence: 66%